Cytokeratin (CK5, CK8, CK14) expression and presence of progenitor stem cells in human fetal thymuses. Issue 6 (13th June 2016) - Gupta, Richa; Gupta, Tulika; Kaur, Harjeet; Sehgal, Shobha; Aggarwal, Anjali; Kapoor, Kanchan; Sharma, Anshu; Sahni, Daisy; Singla, Suhalika
Abstract : The aim of the current study was to observe the expression of cytokeratins in human fetal thymuses. Specific cytokeratin markers in adult humans and mice have been well described but there has been little similar work on human fetuses. We also aimed to see whether progenitor stem cells that could be harvested to treat various immunodeficiency disorders are present in fetal thymic tissue. Thymuses obtained from 30 aborted human fetuses (12 to 31 weeks) were examined immunohistochemically to investigate changes in cytokeratin expression in the epithelial cells (TEC) at various gestational ages. Before 16 weeks of gestation, cortical (cTEC) and medullary (mTEC) TEC exhibited homogenous staining for cytokeratins CK8 and CK5. After 16 weeks there was differential staining, with cTEC positive for CK8 and mTEC for CK5 and CK14. Interestingly, both CK5 + CK8+ progenitor stem cells were present in the fetal thymic cortex at all gestational ages, with a relatively high number from 12 to 16 weeks. Cytokeratin expression in fetal thymuses was quite different from that in the adult thymus owing to the presence of undifferentiated progenitor stem cells in fetal thymic stroma along with differentiated TEC. The best time to harvest these progenitor stem cells from fetal thymic stroma in order to treat various immune deficiency disorders appears to be 12–16 weeks. Clin. Anat. 29:711–717, 2016. © 2016 Wiley Periodicals, Inc.